2008
DOI: 10.1016/j.neulet.2008.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of CaMKII in the nucleus accumbens shell decreases enhanced amphetamine intake in sensitized rats

Abstract: Microinjection of the calcium/calmodulin-dependent protein kinase II (CaMKII) inhibitor KN-93 into the nucleus accumbens (NAcc) shell impairs expression of the sensitized locomotion and NAcc dopamine (DA) overflow normally observed in psychostimulant-exposed rats. Based on these results, we investigated the effect of NAcc shell KN-93 on the enhanced amphetamine (AMPH) intake normally observed in AMPH-relative to saline-exposed rats. Rats were administered five injections of either AMPH (1.5 mg/kg, i.p.) or sal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 21 publications
3
36
0
Order By: Relevance
“…The magnitude of these effects was similar to previous studies (Barak et al, 2013;Neasta et al, 2010). These findings are interesting given that dopamine D1-like agonists increase AMPAR insertion into NAC MSNs through a process involving CAMKIIa (Anderson et al, 2008;Sun et al, 2008) and that both dopamine and CAMKIIa have been shown to be important for the expression of psychostimulant sensitization and drugseeking behavior (Licata and Pierce, 2003;Loweth et al, 2008;Pierce et al, 1998). In fact, lentiviral-mediated knockdown of CAMKIIa in the NACsh reduced motivation to self-administer cocaine on a PR schedule (Wang et al, 2010a).…”
Section: Intra-cerebroventricular Mtorc1 Inhibition Reduces Pr Responsupporting
confidence: 86%
“…The magnitude of these effects was similar to previous studies (Barak et al, 2013;Neasta et al, 2010). These findings are interesting given that dopamine D1-like agonists increase AMPAR insertion into NAC MSNs through a process involving CAMKIIa (Anderson et al, 2008;Sun et al, 2008) and that both dopamine and CAMKIIa have been shown to be important for the expression of psychostimulant sensitization and drugseeking behavior (Licata and Pierce, 2003;Loweth et al, 2008;Pierce et al, 1998). In fact, lentiviral-mediated knockdown of CAMKIIa in the NACsh reduced motivation to self-administer cocaine on a PR schedule (Wang et al, 2010a).…”
Section: Intra-cerebroventricular Mtorc1 Inhibition Reduces Pr Responsupporting
confidence: 86%
“…Calcium influx through L-type channels activates a family of protein kinases including CaMKII, an enzyme that plays a critical role in several forms of neuronal plasticity including changes induced by repeated cocaine exposure (Licata and Pierce 2003;Giordano et al 2010;Loweth and Vezina 2011). Recent work specifically implicates CaMKII in nucleus accumbens AMPA receptor plasticity produced by repeated noncontingent psychostimulant exposure (Boudreau et al 2009;Loweth et al 2010;Schierberl et al 2011) as well as motivation to self-administer amphetamine (Loweth et al 2008(Loweth et al , 2010. After cocaine self-administration, stimulating D1-like dopamine receptors in the medial nucleus accumbens shell promotes the reinstatement of cocaine seeking by serially stimulating L-type calcium channels and phosphorylation of CaMKII (Anderson et al 2008).…”
Section: Nucleus Accumbens Glua1-containing Ampa Receptors and The Rementioning
confidence: 99%
“…The neuronally enriched calcium/calmodulin-dependent protein kinase II (CaMKII) was identified originally as a DFosB target in NAc after cocaine exposure using genomewide approaches (McClung and Nestler, 2003), and we have recently verified this finding by showing that DFosB binding to the CaMKIIa gene promoter is both necessary and sufficient for the kinase's induction in NAc by cocaine . CaMKII in NAc has been linked to altered synaptic function (Huang and Hsu, 2012;Kourrich et al, 2012) and behavioral responses to drugs of abuse (Loweth et al, 2008;Pierce et al, 1998;Robison et al, 2013), but the role of NAc CaMKII in antidepressant action is unknown. Here, we investigated the regulation of NAc CaMKII expression by the antidepressant fluoxetine in the context of chronic social defeat stress.…”
Section: Introductionmentioning
confidence: 99%